Discovery of tanshinone derivatives with anti-MRSA activity via targeted bio-transformation - Wenni He; Miaomiao Liu; Pei Huang; Wael M. Abdel-Mageed; Jianying Han; Jeramie D. Watrous; Don D. Nguyen; Wenzhao Wang; Fuhang Song; Huanqin Dai; Jingyu Zhang; Ronald J. Quinn; et al. (Synthetic and Systems Biotechnology, 2016)
Two potent anti-MRSA tanshinone glycosides (1 and 2) were discovered by targeted microbial biotransformation, along with rapid identification via MS/MS networking. Serial reactions including dehydrogenation, demethylations, reduction, glycosylation and methylation have been observed after incubation of tanshinone IIA and fungus Mucor rouxianus AS 3.3447. In addition, tanshinosides B (2) showed potent activities against serial clinical isolates of oxacillin-resistant Staphylococcus aureus with MIC values of 0.78 μg/mL. This is the first study that shows a significant increase in the level and activities of tanshinone glycosides relative to the substrate tanshinone IIA.